แนวทางการเลือกข้อกำหนดตามมาตรฐาน LEED ในการพัฒนาโครงการศูนย์กระจายสินค้าในเขตกรุงเทพมหานครและจังหวัดโดยรอบ - ภวัต สถิตกาญจนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The development of distribution centers in Thailand that comply with green building standards, particularly regarding LEED certification, is increasing due to developer investment. Therefore, this research aims to study the characteristics of selection requirements according to LEED certifications and the factors influencing the selection requirements. Data were collected from secondary data, as well as interviews with project developers and project users from case studies representing each certification level, including certified, silver, and gold. Finally, the gathered data were analyzed through expert interviews to provide recommendations for selection requirements for distribution center projects according to LEED standards.               The study found that distribution centers located close to the Bangkok Metropolitan Area have a higher chance of achieving higher certification levels and scores compared to those located further away. The characteristics of selecting credits in distribution centers that received LEED certification can be categorized into three levels as follows: 1) projects with the certified level focused on credits that benefit from reducing water and electricity expenses; 2) projects with silver level focus on credits that improve staff transportation and enhance building efficiency through testing and commissioning processes; 3) projects with the gold level focus on credits that improve indoor air quality for staff and reduce external pollution for surrounding communities. The characteristics gathered from interviews with project developers, project users, and green building consultant specialists can be summarized as follows: 1) the credit categories that consistently receive the highest average scores are energy and atmosphere, water efficiency, and location and transportation; 2) the factors influencing the selection of credits include alignment with the company s project development direction and utilizing equipment and construction materials that meet the credit requirements; 3) the factors that limit the selection of credits include town planning and infrastructure constraints, cost and time impact, and conflicts with operational or safety procedures.               In summary, this research explores the characteristics of the selection requirements and the factors influencing the decision to select or not select requirements from the perspective of developers. The findings of this study can be beneficial to green building consultant specialists and developers, as they can use the recommendations and suggestions provided to adapt their project planning for distribution centers. These adaptations aim to address the needs of developers, users, surrounding communities, and the environment, especially for projects seeking LEED certification in the Bangkok Metropolitan Area and surrounding provinces.